Variation in the number and area of palm trees between 2000 and 2024 in Basra Governorate (Journal of the College of Basic Education, 2026)
It is clear from the study and analysis of the variation in the numerical and spatial change planted between the two study years 2000 and 2024, that the number of palm trees in 2000 was high at (3,023,739) palm trees, and these numbers decreased in 2024 to (2,566,345) palm trees. Through the spatial distribution, it appears that the agricultural change in the number of palm trees tends to be concentrated in the western part of Basra Governorate, in Al-Zubair District, as this district had the highest standard degree in terms of high spatial values, while the other districts had less in terms of low spatial values. As for the spatial change in the cultivation of palm trees in Basra Governorate between the two study years, the areas planted with palm trees increased from (80,000) dunums during the year 2000 to (168,047.9) dunums, with an absolute increase of (88,048) and a change amounting to (110.1). Through the distribution Spatially, it appears that the spatial variation in palm tree cultivation tends to be concentrated in the western and eastern parts of Basra Governorate, and a challenge in the Shatt al-Arab and al-Zubair districts, as these two districts had the highest standard score in spatial values, while the other districts had lower scores in spatial values. Accordingly, the variation in the number of palm trees between the two study years, despite the increase in area in 2024, can be explained by several factors, including environmental deterioration in recent years, such as increased salinity in the water and climate change, which has led to a decline in palm productivity or death despite the availability of a larger agricultural area. Water resource depletion, urban expansion, and diseases and pests that affect palm trees, such as the red palm weevil, may have played a role in the decline in palm numbers. Changes in agricultural patterns have led to the use of land for other crops instead of palm trees. All of these factors indicate that an increase in agricultural area does not necessarily mean an increase in palm numbers, as environmental and economic conditions directly affect agricultural production and thus determine the ability to cultivate and maintain palm trees.